2015
DOI: 10.1017/s147054271400021x
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Asymmetries Do Matter! A Corpus Study of German Word Order

Abstract: This article addresses the question of whether the influence of thematic roles (in particular, experiencers and patients) on word order is an epiphenomenal effect of other factors (such as information structure and animacy). For this purpose, I have investigated argument realization with different verb classes, including canonical verbs and either agentive or nonagentive experiencer-object verbs with varying case marking (dative or accusative), in a large corpus of written German. The obtained results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
0
15
1
Order By: Relevance
“…For the remaining 171 examples with an animate object and an inanimate subject, both occurring within the middle field, 23% of the sentences occurred with OS order and 77% with SO order. For a set of 82 sentences in which both subject and object were animate, a strong SO preference emerged, as in the study of Verhoeven (2015). For sentences with inanimate subject and animate object, the results for the object-experiencer psych verbs clearly differ from the results for the agentive verbs, for which not a single OS sentence was found.…”
Section: Comparison Of Experimental Data To Corpus Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…For the remaining 171 examples with an animate object and an inanimate subject, both occurring within the middle field, 23% of the sentences occurred with OS order and 77% with SO order. For a set of 82 sentences in which both subject and object were animate, a strong SO preference emerged, as in the study of Verhoeven (2015). For sentences with inanimate subject and animate object, the results for the object-experiencer psych verbs clearly differ from the results for the agentive verbs, for which not a single OS sentence was found.…”
Section: Comparison Of Experimental Data To Corpus Resultsmentioning
confidence: 82%
“…This was true independently of animacy. In a recent corpus study, Verhoeven (2015) found a moderate preference for middle field-internal OS order for accusative object-experiencer verbs when the object was animate and the subject inanimate. When both were animate, in contrast, a strong preference for SO was observed.…”
Section: Comparison Of Experimental Data To Corpus Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Dative experiencers generally show stronger psych effects than accusative experiencers. For languages such as German and Dutch, this intuition has been supported by empirical findings on experiencer-first effects in Kempen and Harbusch (2003), Haupt et al (2008), Bader and Häussler (2010a), Lamers and de Hoop (2014), Lamers and de Schepper (2010), and Verhoeven (2015). Another type of variation is accusative EO verbs, which appear in different aspectual structures.…”
Section: Backward Binding As a Psych Effectmentioning
confidence: 79%